PRESUPPOSITION IN KIM NAMJOON’S SPEECH AT UNITED NATION GENERAL ASSEMBLY - Sayyidah Aminah (PROJECT (Professional Journal of English Education), 2021)
This research entitled ”Presupposition in Kim Nam Joon’s Speech at United Nation General Assembly. It is a descriptive analysis of speech that used types of presuppositions”. The objectives of this research are to know the types of presupposition and to find out the most dominant type of presupposition in the speech of Kim Namjun. The research method used qualitative descriptive and it is used to analyse the speech as a sample based on Guswita & Widodo's theory. They mention that six types of presupposition, there are; existential presupposition, factive presupposition, lexical presupposition, structural presupposition, non-factive presupposition, and counterfactual presupposition. In analyzing, the research watched the speech which lasts about six minutes, then transcribed, and analysed based on Guswita & Widodo's theory (2019). The result of this study shows that there are four types of presupposition in the speech; existential presuppositions, lexical presupposition, non-factive presupposition, and structural presupposition. With the percentage of existential is 20 or 62.05%, lexical are 9 or 28, 12%, structural are 2 or 6.25 %, and the last non-factive is just 1 or 3,12%. So, the most dominant type is commonly used in the Kim Namjun’s Speech at UNs General Assembly is existential presuppositions. Keywords:  Presupposition, UN’ General Assembly, Kim Namjoon’s Speech